YES(?, pow(2, 2*a + 1) + 4*a + 4) Initial complexity problem: 1: T: (1, 1) f(a, b, c) -> g(a, 1, 0) (?, 1) g(a, b, c) -> g1(a - 1, b, b) [ a > 0 ] (?, 1) g1(a, b, c) -> g(a, c + b, c) (?, 1) g(a, b, c) -> h(a, b, c) [ a <= 0 ] (?, 1) h(a, b, c) -> h(a, b - 1, c) [ b > 0 ] start location: f leaf cost: 0 A polynomial rank function with Pol(f) = 1 Pol(g) = 1 Pol(g1) = 1 Pol(h) = -1 orients all transitions weakly and the transition g(a, b, c) -> h(a, b, c) [ a <= 0 ] strictly and produces the following problem: 2: T: (1, 1) f(a, b, c) -> g(a, 1, 0) (?, 1) g(a, b, c) -> g1(a - 1, b, b) [ a > 0 ] (?, 1) g1(a, b, c) -> g(a, c + b, c) (1, 1) g(a, b, c) -> h(a, b, c) [ a <= 0 ] (?, 1) h(a, b, c) -> h(a, b - 1, c) [ b > 0 ] start location: f leaf cost: 0 A polynomial rank function with Pol(f) = 2*V_1 - 1 Pol(g) = 2*V_1 - 1 Pol(g1) = 2*V_1 Pol(h) = 2*V_1 - 1 orients all transitions weakly and the transition g(a, b, c) -> g1(a - 1, b, b) [ a > 0 ] strictly and produces the following problem: 3: T: (1, 1) f(a, b, c) -> g(a, 1, 0) (2*a + 1, 1) g(a, b, c) -> g1(a - 1, b, b) [ a > 0 ] (?, 1) g1(a, b, c) -> g(a, c + b, c) (1, 1) g(a, b, c) -> h(a, b, c) [ a <= 0 ] (?, 1) h(a, b, c) -> h(a, b - 1, c) [ b > 0 ] start location: f leaf cost: 0 Repeatedly propagating knowledge in problem 3 produces the following problem: 4: T: (1, 1) f(a, b, c) -> g(a, 1, 0) (2*a + 1, 1) g(a, b, c) -> g1(a - 1, b, b) [ a > 0 ] (2*a + 1, 1) g1(a, b, c) -> g(a, c + b, c) (1, 1) g(a, b, c) -> h(a, b, c) [ a <= 0 ] (?, 1) h(a, b, c) -> h(a, b - 1, c) [ b > 0 ] start location: f leaf cost: 0 A polynomial rank function with Pol(h) = V_2 and size complexities S("h(a, b, c) -> h(a, b - 1, c) [ b > 0 ]", 0-0) = a S("h(a, b, c) -> h(a, b - 1, c) [ b > 0 ]", 0-1) = pow(2, 2*a + 1) S("h(a, b, c) -> h(a, b - 1, c) [ b > 0 ]", 0-2) = pow(2, 2*a + 1) S("g(a, b, c) -> h(a, b, c) [ a <= 0 ]", 0-0) = a S("g(a, b, c) -> h(a, b, c) [ a <= 0 ]", 0-1) = pow(2, 2*a + 1) S("g(a, b, c) -> h(a, b, c) [ a <= 0 ]", 0-2) = pow(2, 2*a + 1) S("g1(a, b, c) -> g(a, c + b, c)", 0-0) = a S("g1(a, b, c) -> g(a, c + b, c)", 0-1) = pow(2, 2*a + 1) S("g1(a, b, c) -> g(a, c + b, c)", 0-2) = pow(2, 2*a + 1) S("g(a, b, c) -> g1(a - 1, b, b) [ a > 0 ]", 0-0) = a S("g(a, b, c) -> g1(a - 1, b, b) [ a > 0 ]", 0-1) = pow(2, 2*a + 1) S("g(a, b, c) -> g1(a - 1, b, b) [ a > 0 ]", 0-2) = pow(2, 2*a + 1) S("f(a, b, c) -> g(a, 1, 0)", 0-0) = a S("f(a, b, c) -> g(a, 1, 0)", 0-1) = 1 S("f(a, b, c) -> g(a, 1, 0)", 0-2) = 0 orients the transition h(a, b, c) -> h(a, b - 1, c) [ b > 0 ] weakly and the transition h(a, b, c) -> h(a, b - 1, c) [ b > 0 ] strictly and produces the following problem: 5: T: (1, 1) f(a, b, c) -> g(a, 1, 0) (2*a + 1, 1) g(a, b, c) -> g1(a - 1, b, b) [ a > 0 ] (2*a + 1, 1) g1(a, b, c) -> g(a, c + b, c) (1, 1) g(a, b, c) -> h(a, b, c) [ a <= 0 ] (pow(2, 2*a + 1), 1) h(a, b, c) -> h(a, b - 1, c) [ b > 0 ] start location: f leaf cost: 0 Complexity upper bound pow(2, 2*a + 1) + 4*a + 4 Time: 0.246 sec (SMT: 0.234 sec)